Membangun Komunitas Berbasis Welas Asih: Peran Buddhisme Humanistik Foguangshan dalam Pendidikan di Indonesia - Tegar Yusteditera; Asih , Situ; Dwi Hatmono, Prihadi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study discusses the role of FoGuangShan Humanistic Buddhism in building compassion-based communities through education in Indonesia. As one of the schools of modern Buddhism, FoGuangShan transmits the values of compassion, wisdom, and humanity in educational practices, both formal and informal. Using a qualitative descriptive approach, this study explains how these values are applied in curriculum, learning activities, and social programs involving interfaith and cultural communities. The results of the study show that education based on Humanistic Buddhism plays an important role in fostering tolerance, strengthening moral character, and encouraging social solidarity in Indonesia's multicultural environment. Furthermore, FoGuangShan managed to create a learning space that not only focuses on academic knowledge, but also on the development of empathy, social skills, and collective awareness for living in harmony. In addition, an inclusive and dialogical approach to education is able to strengthen social relations between individuals and minimize potential conflicts based on religious and cultural differences. These findings confirm that the educational model implemented by FoGuangShan can be a significant contribution to the development of character education, interfaith dialogue, and the strengthening of social cohesion in a pluralistic society in Indonesia, as well as an alternative reference for human values-based educational practices.